Impact of information system and blockchain on organizational learning effectiveness - Turi, Jamshid Ali; Al Adresi, Alaeldeen Saleh; Mohd Ridzuan, Darun; Fatimah, Mahmud (Kassel University Press GmbH, 2020)
Focus of the paper was to investigate the impact of information system and blockchain technology on organizational learning effectiveness. Data was collected from the information system faculty and administrative staff of two different universities in Pakistan. Qualitative approach was used to get the objectives of the study. The paper discovered why and how faculty and administrators show resistance or exert influences or assist information system and block chain initiatives in organizational learning effectiveness and sustainability. Qualitative approach was used in the study to comprehend the recurring phenomenon. Finding of the research demands the support of the senior faculty members, administrators and most importantly of the leadership, in the design, orientation and implementation of information system and blockchain for the organizational learning effectiveness.